A continuum damage and discrete crack-based approach for fatigue response and residual strength prediction of notched laminated composites. (June 2017) - Fang, Eugene; Cui, Xiaodong; Lua, Jim
This paper presents a combined continuum damage and discrete crack (CDDC) modelling approach for fatigue damage characterization and post-fatigue residual strength prediction of laminated composite components with a hole. In order to capture both the fatigue cycle-driven material degradation and discrete damage-induced stress concentration and redistribution, an overlapped element approach is developed based on a combined user-defined material (UMAT) and user-defined element (UEL). An Abaqus element coupled with UMAT for fatigue damage characterization is used to detect the location of failure initiation, while the discrete crack network-based (DCN) UEL is applied to insert a crack without remeshing. The intensified stress field induced by the newly inserted matrix crack is used for the evaluation of failure initiation and stiffness degradation. The UMAT for the fatigue analysis has incorporated the stress-cycle ( S-N ) curves for the damage evolution characterization associated with matrix and fiber based on the tested S-N curves for plies at their different orientations. A continuum damage mechanics (CDM) approach is used for the fatigue-driven delamination initiation and propagation by insertion of a finite thickness interface layer at each ply interface. Both the blind and recalibrated predictions are performed for specimens of three different layups under the Air Force Tech Scout 1 program. The predicted fatigue failure progression and the stiffness against cycle curves are compared with the test data provided by the Air Force Research Lab (AFRL). In addition, post-fatigue residual strength predictions are performed for these notched specimens under tension and compression.